Income distribution and social expenditures: A crossnational perspective - Jonathan Schwabish; Timothy M. Smeeding; Lars Osberg (Luxembourg Income Study (LIS), 2004)
We assemble data from several different sources to examine the cross-national effects of inequality and trust on social expenditures. We find that the inequality between the middle classes and the poor (as measured by the 50/10 percentile ratio) has a small, positive impact in social spending; but inequality between the ends of the distribution and middle class (measured by the 90/50 percentile ratio) has a large and negative impact on social spending. Different measures of trust are shown to have a large and positive impact on spending, implying that more cohesive, trusting societies are more willing to share economic resources with others not so fortunate. Our results suggest that as the 'rich' become more distant from the middle and lower classes, they find it easier to opt out of public programs and to buy substitutes for social insurance in the private market. This funding implies that over time rising inequality will erode support for social institutions and social spending that provides insurance against income loss, upward mobility for the disadvantaged, and equality of opportunity for all citizens.
Keywords: 330